Housing and Husbandry Factors Affecting Zebrafish (Danio rerio) Novel Tank Test Responses: A Global Multi-Laboratory Study - Parker, Matthew (2024)
The reproducibility crisis in bioscience, characterized by inconsistent study results, impedes our understanding of biological processes and global collaborative studies offer a unique solution. This study is the first global collaboration using the zebrafish (Danio rerio) novel tank test, a behavioral assay for anxiety-like responses. We analyzed data from 20 laboratories worldwide, focusing on housing conditions and experimental setups. Our study included 488 adult zebrafish, tested for 5 min, focusing on a variety of variables. Key findings show females exhibit more anxiety-like behavior than males, underscoring sex as a critical variable. Housing conditions, including higher stocking densities and specific feed types, influenced anxiety levels. Optimal conditions (5 fish/L) and nutritionally rich feeds (e.g., rotifers), mitigated anxiety-like behaviors. Environmental stressors, like noise and transportation, significantly impacted behavior. We recommend standardizing protocols to account for sex differences, optimal stocking densities, nutritionally rich feeds, and minimizing stressors to improve zebrafish behavioral study reliability.